Critical reflections on the internationalisation of the curriculum - Whitsed, Craig; Green, W. (2015)
© 2015 Sense Publishers. All rights reserved. The concept is very well, but how do I get started? I understand the idea, but I can't see what’s behind it. I can’t find a direction. It’s all too abstract, ideological even. It doesn’t take you anywhere (Anon). We commenced this volume with these words spoken by a disciplinary academic reflecting on internationalisation of the curriculum. The sense of frustration is palpable. And, as the chapters collected in this book indicate, this sense of frustration is not uncommon. While the importance of internationalisation of the curriculum (IoC), as a concept, is increasingly recognised, it is not generally embraced enthusiastically within faculties. Many academics struggle to ‘see what is behind the concept’, ‘get started’, ‘find direction’, or achieve tangible, sustainable outcomes. Our intention in editing this book was to illuminate some of the myriad ways in which this challenge can be addressed.